Sumbangsih Etika John Frame dalam Mengisi Pengharapan Masyarakat 5.0 di Era Revolusi Industri 4.0 - Sutjipto Subeno (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2020)
The emergence of the Industrial Revolution 4.0 has led to the disruption of various fields of life, including the field of ethics. This threat of disruption initiated the hope of the formation of Society 5.0 which is expected to produce an advanced, high-tech, prosperous and moral global society. This expectation needs to be criticized, because it seems that there is not enough ethical discussion that has been elaborated in the thinking of the Society 5.0. The Christian faith (Reformed) sees the importance of ethical aspects in society, because human life cannot be separated from ethical problems and judgments. John Frame's ethical concept which has three perspectives: normative, situational, and existential, can fill this gap for every Christians to go through Industrial Revolution 4.0 era.